Relevance of industrial cultivation of probiotic microorganism Lactobacillus rhamnosus GG - Hryshchenko, Maryna; Starovoitova, Svitlana (My University, 2023)
Today, representatives of the genus Lactobacillus are among the microorganisms that most satisfy probiotic requirements. Among quite a large number of probiotic microorganisms of this genus, we will stop at L. rhamnosus GG - a gram-positive bacterium belonging to the genus Lactobacillus, family Lactobacillaceae. It is of human origin, has sufficient antagonistic activity in relation to pathogenic and opportunistic organisms, is resistant to the action of acids and enzymes of the gastrointestinal tract, has good adhesion, stable genetic characteristics and has no antigenic properties in relation to the human body and belongs to GRAS representatives. The key factor in choosing a biological agent was the scientifically confirmed data that LGG is the only strain of lactobacilli that reduces the duration of rotovirus infection by stimulating the synthesis of immunoglobulin A.// Сьогодні представники роду Lactobacillus є одними з мікроорганізмів, які найбільше задовольняють пробіотичні потреби. Серед досить великої кількості пробіотичних мікроорганізмів цього роду ми зупинимося на L. rhamnosus GG - грампозитивної бактерії, що відноситься до роду Lactobacillus, сімейства Lactobacillaceae. Має людське походження, має достатню антагоністичну активність по відношенню до патогенних і умовно-патогенних організмів, стійкий до дії кислот і ферментів шлунково-кишкового тракту, має хорошу адгезію, стабільні генетичні характеристики і не має антигенних властивостей по відношенню до організму людини. і належить представникам GRAS. Ключовим фактором при виборі біологічного препарату стали науково підтверджені дані про те, що LGG є єдиним штамом лактобактерій, який скорочує тривалість ротовірусної інфекції шляхом стимуляції синтезу імуноглобуліну А.
Keywords: probiotic; cultivation; Lactobacillus rhamnosus GG; кафедра біотехнології і мікробіології; пробіотики; культивування